Youth Engagement in the Community: The ethics of inclusion and exclusion - Lekies, Kristi (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2009)
This study focuses on the engagement of children and youth in their communities and the ways they are included in and excluded from community life. Using a content analysis of a small town United States newspaper over a one-year period, examples of engagement were identified and classified into 12 categories: programs, clubs and special events; fundraising and community service; business and community support; participation in community events; school events; athletic and other performances; employment; involvement in local planning and decision making; serving as a community representative; visibility and recognition; criminal activity and accidents; and use of public space. Examples of community exclusion were identified as well. Young people were engaged primarily through activities that were adult-directed or supervised, or organized through schools, churches, and youth clubs. There was little involvement in local planning, decision making, or activism. Some evidence existed of peer teaching, leadership, and self-initiated activities, as well as intentional efforts by adults to give youth a greater voice in community activities. Implications include several ethical issues regarding the role of young people in community life, particularly young children, and the need for greater awareness on the part of communities of the contributions young people can make.